Improved glass forming ability and soft magnetic properties by minor Mo alloying in Fe–P–C–B–Si bulk metallic glasses. (December 2021) - Shen, Ningning; Li, Yuluo; Dou, Zhengxu; Lv, Kuang; Duan, Mengnan; Li, Fushan; Wu, Yidong; Wang, Yanli; Hui, Xidong
Abstract: The glass forming ability (GFA), mechanical, corrosion resistance and soft magnetic properties of Fe76- x P8 C6 B6 Si4 Mo x ( x  = 0, 0.5, 1, 1.5 and 2 at. %) bulk metallic glasses (BMGs) were investigated. It was shown that the GFA of this BMGs system is greatly enhanced from the critical diameter of 1 mm for base alloy to 5 mm for the alloy with the addition of 2 at. % Mo. The highest fracture strength of the BMG with 1.5 at. % Mo alloying reached 3.1 GPa. The corrosion resistance featured by corrosion voltage and current density and the passivating ability of these BMGs was obviously improved as minor Mo was added. The Mo-alloyed alloys exhibited excellent magnetic properties, e.g., Fe75.5 P8 C6 B6 Si4 Mo0.5 BMG has an ultra-low coercivity as low as 1.45 A/m combined with high saturation magnetization of 1.41 T and effective permeability of about 5700 at 1 kHz. The mechanism for the excellent GFA and soft magnetic properties led by minor Mo alloying was discussed in detail. It is believed that these BMGs have great potential for future industrial applications, such as the fabrication of high-frequency soft magnetic composite materials. Graphical abstract: Image 1 Highlights: Novel Fe–P–C–B–Si–Mo BMGs combine excellent GFA and magnetic properties. The GFA of Fe–P–C–B–Si–Mo BMGs can be greatly enhanced by minor Mo alloying. The B s and H c of Fe75.5 P8 C6 B6 Si4 Mo0.5 BMG with D c of 4 mm are 1.41 T and 1.45 A/m.